Wood and iron exploitation in the Pyrenean highlands during the Visigothic period: the case of the Puymorens pass and the Carol valley, France - Pagès, Gaspard; Jolly-Saad, Marie-Claude (Frontiers in Environmental Archaeology, 2024)
The Puymorens iron mine is located at an altitude of between 2,100 and 2,200 m at the western edge of the Pyrénées-Orientales department (France), which is bordered by the Ariège department in France and Andorra to the west and Spain to the south. It is the highest-altitude iron ore exploitation in the Pyrenees mountains. A major transportation corridor facilitating the north to south crossing of the Pyrenean massif passes by the foot of the mine, from the Ariège valley to the Carol valley. The mine is known to have been in operation from the seventeenth century to the end of the 1960's, and it supplied ore to many modern smelting sites in Andorra, Catalonia and Ariège. New data acquired from the FEDER FERMAPYR and PCR FERAPO programs have enabled the identification of older ironworks in the neighboring Carol valley, which also used this ore and have been radiocarbon dated between the fourth and the sixth centuries. By placing this series of Visigothic smelting sites in their environmental context, we will be able to describe their technical specificities and the impetuses for the early exploitation of iron ore and wood at high altitudes in the Pyrenees. The study will be based as much on the results of archaeological excavations and surveys as well as on anthracology studies to understand the relation between iron ore smelting and the forest exploitation for charcoal production.